Violence against people with disability in England and Wales: findings from a national cross-sectional survey. - Hind Khalifeh; Louise M Howard; David Osborn; Paul Moran; Sonia Johnson (PLoS ONE)
Background The recent World Report on Disability highlighted violence as a leading cause of morbidity among disabled people. However, we know little about the extent to which people with disability experience different violence types, and associated health/economic costs. The recent introduction of disability measures into the England&Wales victimization survey provided an opportunity to address this gap. Methods and findings Analysis of the 2009/10 British Crime Survey (BCS), a nationally representative cross-sectional survey of 44,398 adults living in residential households in England&Wales. Using multivariate logistic regression, we estimated the relative odds of being a victim of past-year violence (physical/sexual domestic or non-domestic violence) in people with disability compared to those without, after adjusting for socio-demographics, behavioural and area confounders. 1256/44398(2.4%) participants had one or more disabilities including mental illness ('mental illness') and 7781(13.9%) had one or more disabilities excluding mental illness ('non-mental disability'). Compared with the non-disabled, those with mental illness had adjusted relative odds (aOR) of 3.0(95% confidence interval (CI) 2.3-3.8) and those with non-mental disability had aOR of 1.8(95% CI: 1.5-2.2) of being a victim of past-year violence (with similar relative odds for domestic and non-domestic violence). Disabled victims were more likely to suffer mental ill health as a result of violence than non-disabled victims. The proportion of violence that could be attributed to the independent effect of disability in the general population was 7.5%(CI 5.7-9.3%), at an estimated cost of £1.51 billion. The main study limitation is the exclusion of institutionalised people with disability. Conclusions People with disability are at increased risk of being victims of domestic and non-domestic violence, and of suffering mental ill health when victimized. The related public health and economic burden calls for an urgent assessment of the causes of this violence, and national policies on violence prevention in this vulnerable group.